EFFECTIVE TEACHING OF FOREIGN LANGUAGES TO ELEMENTARY SCHOOL STUDENTS (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
This article explores the effective methods for teaching foreign languages to elementary school students. It emphasizes the importance of early language learning in enhancing cognitive skills, cultural understanding, and communication abilities. Key strategies discussed include interactive and play-based learning, immersive techniques, a focus on listening and speaking, cultural integration, and the use of short, focused lessons. The article also highlights the role of positive reinforcement and parental involvement in fostering a supportive learning environment. Challenges such as limited resources and inconsistent exposure are addressed with practical solutions. The conclusion underscores the long-term benefits of early language education in preparing students for a globalized world.